Ubiquitous Knowledge Discovery Challenges, Techniques, Applications - May, Michael; Saitta, Lorenza; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Knowledge discovery in ubiquitous environments is an emerging area of research at the intersection of the two major challenges of highly distributed and mobile systems and advanced knowledge discovery systems. It aims to provide a unifying framework for systematically investigating the mutual dependencies of otherwise quite unrelated technologies employed in building next-generation intelligent systems: machine learning, data mining, sensor networks, grids, peer-to-peer networks, data stream mining, activity recognition, Web 2.0, privacy, user modelling and others. This state-of-the-art survey is the outcome of a large number of workshops, summer schools, tutorials and dissemination events organized by KDubiq (Knowledge Discovery in Ubiquitous Environments), a networking project funded by the European Commission to bring together researchers and practitioners of this emerging community. It provides in its first part a conceptual foundation for the new field of ubiquitous knowledge discovery - highlighting challenges and problems, and proposing future directions in the area of 'smart', 'adaptive', and 'intelligent' learning. The second part of this volume contains selected approaches to ubiquitous knowledge discovery and treats specific aspects in detail. The contributions have been carefully selected to provide illustrations and in-depth discussions for some of the major findings of Part I.
A Blueprint for Ubiquitous Knowledge Discovery -- Introduction: The Challenge of Ubiquitous Knowledge Discovery -- Ubiquitous Technologies -- Resource Aware Distributed Knowledge Discovery -- Ubiquitous Data -- Privacy and Security in Ubiquitous Knowledge Discovery -- A Human-Centric Perspective on Ubiquitous Knowledge Discovery -- Application Challenges for Ubiquitous Knowledge Discovery -- Case Studies -- On-Line Learning: Where Are We So Far? -- Change Detection with Kalman Filter and CUSUM -- A Geometric Approach to Monitoring Threshold Functions over Distributed Data Streams -- Privacy Preserving Spatio-temporal Clustering on Horizontally Partitioned Data -- Nemoz $1 (BA Distributed Framework for Collaborative Media Organization -- Micro Information Systems and Ubiquitous Knowledge Discovery -- MineFleet : The Vehicle Data Stream Mining System for Ubiquitous Environments.s
Keywords: Computer science; Computer communication systems; Algorithms; Data mining; User interfaces (Computer systems).; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; User Interfaces and Human Computer Interaction; Electronic books